2020
DOI: 10.1097/md.0000000000022167
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nicorandil in patients with cardiac syndrome X

Abstract: Background: The prevalence of cardiac syndrome X (CSX) is considerable. Some patients show recurrent angina attacks and have a poor prognosis. However, the knowledge of CSX pathophysiological mechanism is still limited, and the treatment fails to achieve a satisfactory suppression of symptoms. Nicorandil has a beneficial effect on improving coronary microvascular dysfunction (CMD). This study aims to evaluate the clinical effects and safety of nicorandil on CSX patients. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
10
0
1
Order By: Relevance
“…A small randomized study by Zhang et al [63] found significant improvement in CFR after treatment with a combination of fluvastatin and diltiazem compared with fluvastatin or diltiazem alone in patients with angina pectoris and normal epicardial arteries on angiogram. Another randomized study by Yokoyama et al [64] described significant improvement from baseline CFR after treatment with simvastatin but not pravastatin in patients with high cholesterol and a low likelihood of CAD. Based on these studies, the use of statins is recommended for most patients with CMD but especially for the endotype of impaired vasodilation unless severe side effects or contraindications are present.…”
Section: Statinsmentioning
confidence: 99%
“…A small randomized study by Zhang et al [63] found significant improvement in CFR after treatment with a combination of fluvastatin and diltiazem compared with fluvastatin or diltiazem alone in patients with angina pectoris and normal epicardial arteries on angiogram. Another randomized study by Yokoyama et al [64] described significant improvement from baseline CFR after treatment with simvastatin but not pravastatin in patients with high cholesterol and a low likelihood of CAD. Based on these studies, the use of statins is recommended for most patients with CMD but especially for the endotype of impaired vasodilation unless severe side effects or contraindications are present.…”
Section: Statinsmentioning
confidence: 99%
“…Nicorandil, ivabradine, and trimetazidine are drugs under investigation to evaluate their potential role in the treatment of CMD. Nicorandil is a mitochondrial ATP-sensitive potassium channel activator that showed some effects in improving symptoms ( 54 ). A study demonstrated that ivabradine, which selectively reduces sinus node activity, could improve angina in patients with CMD, but without effects on CFR ( 55 ).…”
Section: Management Of Microvascular Anginamentioning
confidence: 99%
“…Finally, a recent meta-analysis on the effects of nicorandil on MVA patients showed its potential of improving angina symptoms, ECG, and endothelial dysfunction. However, due to low-quality evidence among analyzed studies, clinical benefits remained unclear [185].…”
Section: Endothelin Receptor Antagonist Endothelin (Et-1) Increases V...mentioning
confidence: 99%